Novel estrogen-related gene variants identified by whole-exome sequencing in pregnancy-associated intrahepatic cholestasis - Hua Lai; Siming Xin; Jinliang Zhang; Yang Hu; Wenjuan Fan; Hong Wan; Bowen Chen; Yang Zou; Xiaoming Zeng; Xianxian Liu (Frontiers in Genetics)
Intrahepatic cholestasis of pregnancy (ICP) is associated with an increased risk of adverse fetal outcomes, including fetal morbidity and mortality. It is a complex liver disorder influenced by genetic interactions, estrogen levels, and environmental factors. Although elevated estrogen levels are known to contribute to ICP pathogenesis, the role of genetic variants in estrogen-related genes remains poorly characterized. Accordingly, we conducted whole-exome sequencing (WES) in 249 patients with ICP, focusing on eight key estrogen-related genes (ESR1/2, CYP17A1/19A1, CYP1A2/1B1/3A4, and COMT). Variants were validated by Sanger sequencing and functionally characterized using comprehensive bioinformatics analyses (PolyPhen-2, SIFT, and MutationTaster) combined with molecular modeling. Our whole-exome sequencing analysis of 249 patients with ICP identified 235 variants across eight estrogen-related genes, with three novel CYP17A1 missense mutations (p.Pro28Thr, p.Phe93Leu, and p.Arg347Leu) demonstrating particularly significant findings. These variants exhibited the following characteristics: (1) complete absence in 1,237 controls and all public genomic databases (1000 Genomes, ExAC, and dbSNP); (2) evolutionary conservation of the affected residues, with unanimous pathogenic predictions from all algorithms (PolyPhen-2: damaging; SIFT: deleterious; MutationTaster: disease-causing); (3) molecular modeling demonstrating structural perturbations in critical functional domains, including steroid-binding and redox partner interaction sites. Furthermore, analysis of placental tissue revealed significantly reduced CYP17A1 expression in ICP cases versus controls (P < 0.05), suggesting functional impairment of estrogen metabolic pathways. We identified three novel pathogenic CYP17A1 variants associated with ICP through whole-exome sequencing, elucidated their structural and functional effects on estrogen metabolism, and demonstrated significantly reduced placental CYP17A1 expression, thereby providing crucial insights into the genetic basis of ICP pathogenesis.